2019
DOI: 10.1111/ocr.12354
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical relationship between the maxillary posterior teeth and the sinus floor according to an anterior overbite

Abstract: Objective To evaluate the vertical relationship between the maxillary sinus floor (MSF) and the maxillary posterior teeth (MPT) according to an anterior overbite. Settings and Sample Population The patients were divided into three groups according to an anterior overbite. The open bite group (OBG) included patients with an anterior overbite of ≤0 mm, the normal overbite group (NBG) included patients with an overbite of 0‐3 mm, and the deep bite group (DBG) included patients with an overbite ≥3 mm. Thirty patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Patients were categorized based on their ANB angles of 0 to 4°, ≥ 4°, and ≤ 0° into skeletal classes Class I, II, and III malocclusions, respectively [ 21 ]. Every premolar and molar root was classified into the sagittal and coronal planes based on methods used in previous study [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were categorized based on their ANB angles of 0 to 4°, ≥ 4°, and ≤ 0° into skeletal classes Class I, II, and III malocclusions, respectively [ 21 ]. Every premolar and molar root was classified into the sagittal and coronal planes based on methods used in previous study [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The vertical relationship between the MSF and the PMT was analyzed. When premolars had two roots, the closest root to the MSF was evaluated [ 22 ]. For each patient, the maxillary right and left first and second premolars and right and left first and second molars in both the sagittal and coronal views were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…A literature search found only a few studies that evaluated the distance from the maxillary posterior root apices to the MSF in different skeletal patterns. 15 16 17 18 …”
Section: Discussionmentioning
confidence: 99%
“…Son et al 18 divided 30 subjects into open bite, normal overbite, and deep bite groups and evaluated the distance from the maxillary posterior root apices to the MSF using CBCT. Their results showed that the open bite group had shorter distances from the maxillary posterior root apices to the MSF than the deep bite group.…”
Section: Discussionmentioning
confidence: 99%
“…The distance between the maxillary sinus (MS) and maxillary posterior teeth has been known to cause greater tipping, and moving teeth against the MSW can induce root resorption [ 3 ]. It is generally believed that moving teeth against the cortical bone is very difficult and will increase the complexity and duration of orthodontic treatment in adult patients [ 1 , 2 , 4 , 5 ]. Generally, an inverse relationship exists between bone density and the rate of tooth movement [ 6 ].…”
Section: Introductionmentioning
confidence: 99%